(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2007)
The analysis of the behaviour of austenitic stainless steels, under dynamic stress in physiological medium, remains important in order to determine their lifetime when they are used in implantology. In this purpose, simulations of fatigue corrosion of pre-notched specimens were carried out. Input notch data were taken from stable pits obtained by preliminary polarization tests in a solution of FeCl2, by taking two different concentrations (0,5 and 1M). Calculations were made using effective mechanical and electrochemical conditions observed on human body implants. Two fatigue models have been applied. Höeppner model is only a mechanical one, whereas Newman model adds chemical effect. Numerical results indicates the number of cycles leading to critical size of pits-to-crack transition and then to failure. Furthermore, the effect of the initial notch size on fatigue behaviour of the stainless steel is highlighted. Both models indicate that decreasing initial notch size raises the number of cycles to failure. Adding chemical action to mechanical one accelerates the damage, in general. However, at higher sizes, one can observe a slowing down of the chemical effect. The curve of Wöhler for different mediums and values of applied stress shows that the mechanical action has much more influence when high loads are applied. As the stress applied decreases, the electrochemical effect becomes extensive and reduces considerably the lifetime of material. The prediction of lifetime needs thus to include the effect of other parameters, such as stress frequency, in order to compare it with real implant lifetime.